2017
DOI: 10.1080/0886022x.2017.1348955
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of renal disease in South Korea: a 20-year review of a single-center renal biopsy database

Abstract: Background: Several registries and centers have reported the results of renal biopsies from different parts of the world. As there are few data regarding the epidemiology of glomerulonephritis (GN) in South Korea, we conducted this study on renal biopsy findings during the last 20 years from a single center.Methods: Data for 818 patients who underwent renal biopsy at our center between 1992 and 2011 were collected retrospectively. All kidney specimens were examined with light microscopy (LM) and immunofluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
22
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 54 publications
(46 reference statements)
8
22
1
3
Order By: Relevance
“…Although these data cannot be assumed to be representative of the Korean population, the results are largely compatible with previous studies from Korean patients [1,3,4]. In the current study, thin basement membrane disease previously had an exceptionally high frequency but dramatically declined in recent years.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Although these data cannot be assumed to be representative of the Korean population, the results are largely compatible with previous studies from Korean patients [1,3,4]. In the current study, thin basement membrane disease previously had an exceptionally high frequency but dramatically declined in recent years.…”
supporting
confidence: 91%
“…Therefore, readers should keep these things in mind when they compare the results of studies. Table 1 summarizes the previous publications on frequencies of biopsy-proven renal diseases reported in China, Japan, and South Korea [1][2][3][4][5][6][7][8][9]. These data show major biopsy-proven glomerular diseases in East Asian countries.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies have shown that membranous nephropathy (MN) is the most common cause of adult nephrotic syndrome, whereas minimal change disease (MCD) is the predominant cause of nephrotic syndrome in children [5]. In elderly patients, the relative proportion of crescentic glomerulonephritis (GN), MN, and focal segmental glomerulonephritis (FSGS) is higher than in younger patients [6,7]. Moreover, the prevalence of glomerular disease varies according to the period.…”
Section: Introductionmentioning
confidence: 99%
“…Information on the changing patterns of renal diseases in relation to cause of death is scanty and largely absent in Ghana . This has been attributed to the absence of renal biopsy registries and published autopsy data .…”
mentioning
confidence: 99%